2017
DOI: 10.1007/s13201-017-0561-1
|View full text |Cite
|
Sign up to set email alerts
|

Waste water purification using new porous ceramics prepared by recycling waste glass and bamboo charcoal

Abstract: New porous ceramics (PC) prepared by recycling waste glass bottle of soft drinks (80 mass%) and bamboo charcoal (20 mass%) without any binder was applied to the waste water purification under aeration at 25°C. Artificial waste water (15 L) containing 10 mL of milk was examined by combining 15 mL of activated sludge and 750 g of PC. Biochemical oxygen demand (BOD) showed a marked decrease from 178 to 4.0 (±0.1) mg L -1 in 5 days and to 2.0 (±0.1) mg L -1 in 7 days, which was equal to the Environmental Standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Nishida et al reported on the fabrication of porous glass ceramic by sintering waste soda lime silicate and charcoal for water purification [ 24 ]. The porous glass ceramic produced from their study was successful in removing water turbidity and the pores maintained suitable environments for microbial proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Nishida et al reported on the fabrication of porous glass ceramic by sintering waste soda lime silicate and charcoal for water purification [ 24 ]. The porous glass ceramic produced from their study was successful in removing water turbidity and the pores maintained suitable environments for microbial proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the most appropriate sintering temperature was determined to be 800°C. Related porous ceramics was prepared by recycling the waste glass bottle with bamboo charcoal by sintering a powder mixture with a mass ratio of 80:20 at 800°C for 60 min (Nishida et al 2017a). It is noted that waste glass bottle, i.e., soda-lime silicate glass which was free from heat-resistant Al 2 O 3 , was the main component in these porous ceramics when recycled with wood charcoal or bamboo charcoal.…”
Section: Introductionmentioning
confidence: 99%